Avoiding Frauds and Deception - Carol Fountain; Michael T. Olexa; Jana Caracciolo; Lauren Grant (EDIS)
Disaster victims must be cautious about employing strangers to remove trees and do repair work on their property. Every agreement and credit contract should be read carefully and evaluated before it is signed. Shoddy workmanship and price gouging are common in crises. This 2-page fact sheet is a minor revision written by Michael T. Olexa, Jana Caracciolo, and Lauren Grant, and published by the Food and Resource Economics Department, October 2019.